Edukasi Trading dan Simulasi Transaksi Akun Demo untuk Tingkatkan Literasi Keuangan Mahasiswa - Putri, Jelita Giosika Rahma; Santoso, Bowo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Low financial literacy among students regarding trading in the digital era leads to fears of real capital losses and a gap between theory and practice. Therefore, this community service aims to enhance financial literacy through comprehensive trading education and simulation using a demo account from PT Trijaya Pratama Futures. The implementation method includes socialization at Gedung GKB UPN Veteran Jawa Timur (November 20, 2025) with 25 participants, consisting of material presentations (trading basics, technical analysis, risk management, trusted brokers), demo account opening (100% successful with virtual capital of Rp100,000,000), live trading on XAU/USD, and interactive QA sessions. The results show that participants were able to understand independent trading, manage risks, and handle trading psychology effectively. This activity is crucial for building investment independence among the younger generation safely without real loss risks.